Dental Management of a Child with Incidentally Detected Hemophilia: Report of a Clinical Case - Ricardo Martínez-Rider; Arturo Garrocho-Rangel; Raúl Márquez-Preciado; María Victoria Bolaños-Carmona; Socorro Islas-Ruiz; Amaury Pozos-Guillén (Case Reports in Dentistry)
Children with hemophilia (A or B) are at risk for bleeding episodes, which rank from mild mucosal/soft tissues bleeding to life-threatening hemorrhages. This report describes the dental/medical management provided to an 8.10-year-old patient suffering from uncontrolled bleeding after a surgical procedure to expose both permanent upper central incisors, in which hemophilia was a pure incidental finding. Additionally, diverse precautions to be considered during the dental clinical treatment of hemophilic children are discussed.